Challenges Faced by Novice English Language Teachers in Raparin Territory During Their Initial Years of Teaching - Ameen, Rizgar M.; Zahir, Hawram O.; Majid, Karwx B.; Salam, Binar H. (Journal of Ecohumanism, 2024)
This research is devoted to investigate the challenges faced by novice English language teachers in the Raparin area during their initial years of teaching. Teaching, a process vital worldwide, involves transferring knowledge, skills, and values, and novice teachers often encounter numerous obstacles in this journey. The objective of this study is identifying these obstacles, focusing on classroom management, emotional problems, lesson planning, adaptation to the profession, relational challenges, time management, technological integration, and handling individual student differences. Utilizing a mixed-methods approach, including surveys and interviews with 40 novice teachers, the research reveals that a significant number of these teachers struggle with designing and implementing lesson plans, managing classrooms, and integrating technology effectively. Emotional stress, relational challenges, and insufficient preparation for addressing individual student needs further compound their difficulties. The findings underscore the necessity for targeted support and training programs to enhance novice teachers' competencies and ease their transition into the teaching profession. Addressing these challenges is crucial for improving the quality of education and ensuring the retention and development of novice teachers in the Raparin Territory.